2016
DOI: 10.3386/w22423
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Group Differences in High-Dimensional Choices: Method and Application to Congressional Speech

Abstract: for their comments and suggestions. We thank Frances Lee for sharing her data on congressional communications staff. We also thank numerous seminar audiences and our many dedicated research assistants for their contributions to this project. This work was completed in part with resources provided by the University of Chicago Research Computing Center and the Stanford Research Computing Center. The data providers and funding agencies bear no responsibility for use of the data or for interpretations or inference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 53 publications
(75 reference statements)
0
69
1
1
Order By: Relevance
“…Instead, our approach is to specify a generative model of the data and to measure group differences using objects that have a well‐defined meaning in the context of the model . In the body of the paper, we note some formal connections to the literature on residential segregation, and in an earlier draft, we pursue a detailed application to trends in residential segregation by political affiliation (Gentzkow, Shapiro, and Taddy ()).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, our approach is to specify a generative model of the data and to measure group differences using objects that have a well‐defined meaning in the context of the model . In the body of the paper, we note some formal connections to the literature on residential segregation, and in an earlier draft, we pursue a detailed application to trends in residential segregation by political affiliation (Gentzkow, Shapiro, and Taddy ()).…”
Section: Introductionmentioning
confidence: 99%
“…The rank-order 2 See also Davis et al (2016) and Keane and Wasi (2012) for other applications of sampled logit-type discrete choice models. On a related note, Gentzkow et al (2016) use a Poisson approximation to enable parallel computation of a multinomial logit model of legislators' choices among hundreds of thousands of phrases.…”
Section: Related Literaturementioning
confidence: 99%
“…Evidence has increasingly shown that such differences have an impact on the policies implemented (e.g., Levitt (1996)). Indeed, the language of the two parties is increasingly becoming more differentiated (e.g., Gentzkow, Shapiro and Taddy (2016)). Therefore, in a world of increasing social-cultural polarization, it makes sense to begin by allowing for correlation between policy preferences and sociocultural dis-13 tance.…”
Section: Culturally Differentiated Preferencesmentioning
confidence: 99%
“…This provides a new avenue for empirical exploration, as social sorting may be driving recent ideological divergence within the parties. In particular, the stark results of Gentzkow, Shapiro and Taddy (2016), finding that parties increasingly use particularistic, polarized language which is only intended to reach base voters, should indicate a potential social mechanism for political polarization.…”
Section: Cultural Groups Imperfect Beliefs and Polarizationmentioning
confidence: 99%
See 1 more Smart Citation